Delivery of an Occupation-Focused Cognitive Remediation Therapy Programme in an Aotearoa New Zealand Public Mental Health Service: Case Study Research - Wallis, Katrina (Auckland University of Technology, 2024)
People with enduring psychotic illness face difficulties with attention, memory, information processing, executive functioning and social cognition, which impact on social and occupational functioning. A body of evidence shows that cognitive remediation therapy (CRT) addresses cognitive difficulties. Some secondary mental health services in Aotearoa New Zealand have started delivering CRT with an emphasis on supporting tāngata whai ora (service users/consumers) to embed skills gained through CRT in the context of their day-to-day occupations. However, little is known about what is needed to effectively deliver this intervention. In particular, little is known about the experiences of organisational leaders, therapists and tāngata whai ora who have taken part in the delivery of such a programme. The aim of this study was to gain understanding of how an occupation-focused CRT programme was delivered as a basis for clear recommendations to support an effective roll-out of the programme through Aotearoa New Zealand mental health services. This research therefore asked, How was an occupation-focused CRT programme delivered in a community mental health setting within Aotearoa New Zealand? What were peoples’ experiences of the delivery of the programme? What factors influenced the delivery of the programme and how did those factors shape delivery? Qualitative, constructivist case study methodology was used to address the research questions. Four organisation leaders, five occupational therapists and four tāngata whai ora were interviewed and sixteen documents were reviewed. The interview data was interpreted using reflexive thematic analysis. The documents were analysed using direct interpretation, providing insights into the context of the case. Through an iterative search for correspondence and patterns within the interpretations, the findings from the interviews and documents were brought together to arrive at 14 assertions about the case. The leaders’ experiences of the programme delivery were constructed into two themes. ‘Managing Tensions’ conveys the multiple demands leaders needed to juggle, and ‘Embedding CRT’ describes what the leaders needed when considering delivery of CRT. The therapists' experiences were constructed into five themes. ‘Splicing Occupation and CRT’ conveys therapists combining new knowledge of CRT with existing knowledge of occupational therapy. “Taking the Lead” describes the actions of one therapist in rolling out delivery. Therapists expressed that ‘Strong Relationships were Essential to Delivery’, along with ideas for “Enhancing Future Delivery”. The theme ‘Broken Feedback Loops’ highlights a lack of communication that hindered ongoing delivery. Tāngata whai ora conveyed they were moving forward in their lives captured in one theme ‘Making Way’ with ‘Changes to occupational performance’ highlighted after participating in the programme. Assertions identify complexities that hindered programme delivery including a lack of overarching direction and ineffective communication, and crucial elements required for delivery including leadership, training and facilitating self-determination for tāngata whai ora. The findings have generated six recommendations to help leaders, clinicians and policy makers understand what is needed to support delivery of an occupation-focused CRT programme, including ministerial support, engagement with Māori and an occupational-focus. Further research entailing a broader implementation pilot is recommended, along with CRT research that focuses on tāngata whai ora occupational needs.